Perception of victim treatment by police and courts: A study among university students in India and Japan - Chockalingam Kumaravelu; Srinivasan Murugesan (Temida, 2008)
Previous research has established that the perception of victim treatment is influenced by a number of factors such as socio-demographic characteristics, economic status of the people, prior victimization and so on. Against this background, a study was conducted to examine the factors influencing the perception of victim treatment by police and courts. Data were collected using a structured questionnaire from a sample of 725 students from the city of Chennai (India) and 715 students from the city of Mito in Japan. The results revealed that while some of the factors such as gender, age, religion and community of the respondents have significantly influenced the perception of victim treatment, the effects of place of stay, nativity and income on the perception of victim treatment were not found to be significant.